Performing Toraja rice ritual, communicating biodiversity on YouTube: A study of conservation on rice landrace - Ranteallo, Ikma Citra; Palinggi, Sandryones; Alam, Meredian; Kolopaking, Lala Mulyowibowo; Lubis, Djuara Pangihutan; Zuhud, Ervizal Amir Muhammad; Andilolo, Imanuella Romaputri; Nasution, Azwar Hadi; Arifin, Muchamad Zaenal (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
The proliferating public interest in conservation can be explored by monitoring what people say and what people do on social media platforms. YouTube is one of the resources for digital conservation studies as the users are allowed to archive and share content. Meanwhile, networks visualization provided by computer software is powerful to preserve vernacular languages since text(s) tagging is one of the main processes in gaining data. The present study aims to answer research questions using a transdisciplinary approach to sociology, ethnobotany, and communication science. Thus, this research enquires; (a) how might conservation of Toraja rice landraces be practiced continuously? (b) what are the current forms of conservation that are developed and accepted as Toraja socio-cultural activities? (c) how do social media platforms, YouTube, for instance, contribute to the conservation efforts in rice landraces? (d) what are the social implications of conservation education through social media? In order to answer the above questions, six different research methods, namely, observations, in-depth interview, mapping distribution of rice landrace varieties in six fields of studies, calculating Index of Cultural Significance on rice accessions for practicing conservation rice landrace. Digital conservation and conservation culturomics were also measured using NodeXL and API for visualizing the graph of YouTube videos network and calculating the frequency of words occurrence according to search string Toraja rice ritual. The outcome from the study indicates the current forms of conservation by cultivating and consuming rice landrace varieties on everyday life and ritual, as well as preserving rice and agriculture images on wood carving motifs, folk song, and folk dance. The digital conservation efforts are demonstrated by archiving and broadcasting rice rituals on YouTube videos. With an increase of frequency on word occurrences by Toraja language on hashtags on YouTube videos, the users were contributing to participatory culture for preserving vernacular language and promoting agricultural innovations in digital conservation ecosystems and environmental communication.